Random number generator simulation and digital IC design from inverse congruential algorithm - Ahmad Firdaus Mohd Razy (School of Microelectronic Engineering, University Malaysia Perlis, 2011)
Random number generator is a generation of random number sequence based on random number algorithm, which will produce an unpredictable number of a sequence. This study describes the random number generator simulation for several random number algorithms and designing digital IC random number from Inverse Congruential algorithm for cryptography purpose. In this investigation, the several random number algorithms are selected based on pseudorandom number algorithm and are simulated by theoretical simulator analysis. The theoretical simulation analysis will show result of random number distribution data and random number pattern data. The results indicate of deterministic of sequences and pattern of generating random number. NIST tester is included in this project to evaluate the randomness of a sequence. The algorithm that was selected is Inverse Congruential algorithm based on the performance in theoretical simulation analysis. The test showed that the random number sequences for this algorithm achieved 13.75% of randomness. Meanwhile, result from NIST tester showed that, this algorithm has appeared high in linear complexity. The design of digital IC random number generator was purposely to reducing size of random number generator hardware, and at same time consumes low power and also cheaper in production cost compared to current random number generator hardware that need high cost for cryptographic development.